An empirical study of administrative justice at times of COVID-19 in Italy - Giuseppe Di Vita; Paolo Lorenzo Ferrara; Alessandra Patti (Regional Studies, Regional Science)
This paper investigates the impact of the COVID-19 pandemic on the functioning of the Regional Administrative Courts (TAR) in Italy. For this purpose, we constructed two databases covering the period from 2018 to 2021, gathering macroeconomic and microeconomic data from the TARs of the Italian regions (NUTS-2). Despite the brevity of the period, the availability of data allows us to perform a comprehensive analysis with econometric models for micro and macro data. Empirical findings suggest the existence of two-fold and simultaneous effects of COVID-19 on the efficiency of administrative courts: on one hand, the advent of COVID-19 has led to the reorganisation of courts and related-activities, prolonging the duration of administrative disputes. On the other hand, COVID-19 has introduced measures to limit face-to-face activities, such as holding hearings in person, and adopting information and communications technologies (ICTs) to prosecute judicial activities. This measure proved beneficial to the proper functioning of the Italian TARs by reducing the duration of administrative proceedings. Policy implications indicate that the digitalisation of administrative procedures, not only during COVID-19, is crucial for enhancing the promptness of the administrative disputes of the Italian TARs.